PENGARUH PENGEMBANGAN KARIR DAN IKLIM ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN (STUDI KASUS ALPHA HOTEL PEKANBARU) - Oktriwani "; Kasmirudin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to see the influence of career development and organizational climate on employee job satisfaction Alpha Hotel Pekanbaru. Career development as a variable (X1), organizational climate (X2) and job satisfaction (Y). The method in this research is descriptive and quantitative by using program of SPSS 16, where sample used is employees of Alpha Hotel Pekanbaru with respondent counted 56 people. To determine the number of samples used slovin formula, and t sampling technique by sampling and data collection techniques through questionnaires. The results of analysis using validity test, reliability test, determination test, simple linear regression test, multiple linear regression test, t test and f test. So it can be concluded that career development has a significant effect on employee work satisfaction Alpha Hotel Pekanbaru. Climate organization significant effect on employee work satisfaction Alpha Hotel Pekanbaru. And the influence of career development and organizational climate have a significant effect on employee work satisfaction Alpha Hotel Pekanbaru.Keywords: career development, organizational climate, and employee job satisfaction